Qualitative study on identification of common coping strategies practised by Indigenous Peoples (Orang Asli) in Peninsular Malaysia during periods of food insecurity - Law, Leh Shii; Sulaiman, Norhasmah; Gan, Wan Ying; Mohd Nasir, Mohd Taib (Cambridge University Press (CUP), 2018)
Objective: To examine the types of coping strategies practised by Indigenous women or Orang Asli (OA) in Peninsular Malaysia during times of food shortage and to determine the level of severity for food insecurity that will trigger each specific coping strategy. Design: A qualitative case study was conducted. Pertinent information about each type of coping strategy was gathered by in-depth interviews. To gauge the level of severity for each of the coping strategies, focus group discussions (FGD) were held. Thematic analysis was used for data analysis. Setting: OA villages in the states of Kelantan, Pahang, Perak and Selangor, Malaysia. Subjects: Sixty-one OA women from three ethnic groups (Senoi, Proto-Malay and Negrito) for in-depth interviews and nineteen OA women from the Proto-Malay ethnic group for three FGD. Results: The findings identified twenty-nine different coping strategies and these were divided into two main themes: food consumption (sub-themes of food consumption included dietary changes, diversification of food sources, decreasing the number of people and rationing) and financial management (sub-themes of financial management included increasing household income, reducing expenses for schooling children and reducing expenses on daily necessities). Three levels of severity were derived: less severe, severe and very severe. Conclusions: This information would enable local authorities or non-governmental organisations to more precisely target and plan interventions to better aid the OA communities needing assistance in the areas of food sources and financial management.